Impact of global environmental changes on the range contraction of Eurasian moose since the Late Pleistocene - Magdalena Niedziałkowska; Marcin Górny; Joanna Gornia; Danijela Popović; Mateusz Baca; Urszula Ratajczak-Skrzatek; Oleksandr Kovalchuk; Maciej Sykut; Małgorzata Suska-Malawska; Paweł Mackiewicz; Emilia Hofman-Kamińska; Rafał Kowalczyk; et al. (Science of The Total Environment, 2024)

Magnetic maps in animal navigation - Kenneth J. Lohmann; Kayla M. Goforth; Alayna G. Mackiewicz; Dana S. Lim; Catherine M. F. Lohmann (Journal of Comparative Physiology A, 2022)
In addition to providing animals with a source of directional or ‘compass’ information, Earth’s magnetic field also provides a potential source of positional or ‘map’ information that animals might exploit to assess location. In less than a generation, the idea that animals use Earth’s magnetic field as a kind of map has gone from a contentious hypothesis to a well-established tenet of animal navigation. Diverse animals ranging from lobsters to birds are now known to use magnetic positional information for a variety of purposes, including staying on track along migratory pathways, adjusting food intake at appropriate points in a migration, remaining within a suitable oceanic region, and navigating toward specific goals. Recent findings also indicate that sea turtles, salmon, and at least some birds imprint on the magnetic field of their natal area when young and use this information to facilitate return as adults, a process that may underlie long-distance natal homing (a.k.a. natal philopatry) in many species. Despite recent progress, much remains to be learned about the organization of magnetic maps, how they develop, and how animals use them in navigation.

Redescription of the western Balkan species Xerocampylaea waldemari and its phylogenetic relationships to other Urticicolini (Gastropoda: Hygromiidae) - Małgorzata Proćków; Michael Duda; Luise Kruckenhauser; Wim J. M. Maassen; Anton J. de Winter; Paweł Mackiewicz (Systematics and Biodiversity, 2019)

Content of PAHs in soil of a hazel orchard depending on the method of weed control - S. J. Krzebietke; J. Wierzbowska; P. J. Żarczyński; S. Sienkiewicz; M. Bosiacki; B. Markuszewski; A. Nogalska; E. Mackiewicz-Walec (Environmental Monitoring and Assessment, 2018)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A genetic assessment of parentage in a natural population of dollar sunfish ( Lepomis marginatus ) based on microsatellite markers - M. MacKiewicz; D. E. Fletcher; S. D. Wilkins; J. A. Dewoody; J. C. Avise (Molecular Ecology, 2002)
We employ microsatellite markers to assess mating tactics in Lepomis marginatus . Genetic assignments for 1015 progeny in 23 nests indicate that about 95% of the offspring were sired by their respective nest‐guardians, a finding consistent with the apparent absence of a brood parasitic morphotype in this species. Allopaternal care was documented in two nests, one resulting from a nest takeover, the other from cuckoldry by an adjoining nest‐tender. Clustered de novo mutations also were identified. About 2.5 females (range 1–7) contributed to the offspring pool within a typical nest. Results are compared to those for other Lepomis species.

The genetic mating system of spotted sunfish ( Lepomis punctatus ): mate numbers and the influence of male reproductive parasites - J. A. Dewoody; D. E. Fletcher; M. Mackiewicz; S. D. Wilkins; J. C. Avise (Molecular Ecology, 2000)
In nest‐building fish species, mature males often exhibit one of two alternative reproductive behaviours. Bourgeois males build nests, court females, and guard their eggs. Parasitic cuckolders attempt to steal fertilizations from bourgeois males and do not invest in parental care. Previous evidence from the bluegill sunfish ( Lepomis macrochirus ) suggests that adult males are morphologically specialized for these two tactics. Here, we used microsatellite markers to determine genetic parentage in a natural population of the spotted sunfish ( L. punctatus ) that also displayed both bourgeois and parasitic male morphs. As gauged by relative investments in gonadal vs. somatic tissues, between 5 and 15% of the mature adult males were parasites. Multi‐locus genotypes were generated for more than 1400 embryos in 30 nests, their nest‐guardian males, and for other adults in the population. Progeny in approximately 57% of the nests were sired exclusively by the guardian male, but the remaining nests contained embryos resulting from cuckoldry as well. Overall, the frequency of offspring resulting from stolen fertilizations was only 1.3%, indicating that the great majority of paternity is by bourgeois nesting males. With regard to maternity, 87% of the nests had at least three dams, and computer simulations estimate that about 7.2 dams spawned per nest.